ANALISIS KESULITAN PESERTA DIDIK DALAM MENYELESAIKAN SOAL KONEKSI MATEMATIS - Trinova, Zulvia; Marlina, Leni (Math Educa Journal, 2019)
The purpose of this study was to determine the difficulties experienced by students and the factors that make it difficult for students to answering the questions the mathematical connection of the XI IPA MAN class of Kota Pariaman. The type of research used in this research is descriptive research with  qualitative approach. The subjects of this research were all students of class XI IPA 2 who were enrolled in the first semester of the 2018/2019 academic year. The research source is worked as qualitative data source is consists of 6 students who are distinguished based on mathematical connection ability. Data collection is done through tests and interviews. The results showed that the difficulties of students in answering the questions mathematical connection, namely (1) lack of understanding of the mathematical concepts that had been learned (2) difficulties connections mathematical concepts that were previously known in problems solving (3) difficulties using the principle of inequality in describing the graph of the settlement area (4) lack of mastery of procedures in problems solving verbal or story problems. Factors that cause difficulty in learning mathematics includes; difficulty understanding the meaning of problem, less in understanding the concept; difficulty in counting; carelessness or uncarefuly